2016
DOI: 10.18632/oncotarget.10497
|View full text |Cite
|
Sign up to set email alerts
|

Potential specific immunological indicators for stroke associated infection are partly modulated by sympathetic pathway activation

Abstract: BackgroundEvidence has led to the consideration of immunodepression after stroke as an important contributor to stroke associated infection (SAI). However, so far no specific immunological indicator has been identified for SAI, and the underlying mechanism remains poorly understood.ResultsSAI patients had significantly higher IL-6 and IL-10 levels and lower HLA-DR levels than no-infection patients within 48h after stroke onset. NA significantly increased IL-10 levels, reduced HLA-DR expression, and decreased I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(37 reference statements)
1
8
0
1
Order By: Relevance
“…Subsequently, the interleukin-6 will stimulate the proliferation and differentiation of cells involved in the immune response, thereby enhancing the function of these cells. Finally, through this process, interleukin-6 plays an anti-infective role (44).The results of our study found that interleukin-6 might be used for the prediction of UTI after a stroke is about the same as previous studies (16,17,29).…”
Section: Interleukin-6 Nihss Score and Sexsupporting
confidence: 74%
See 1 more Smart Citation
“…Subsequently, the interleukin-6 will stimulate the proliferation and differentiation of cells involved in the immune response, thereby enhancing the function of these cells. Finally, through this process, interleukin-6 plays an anti-infective role (44).The results of our study found that interleukin-6 might be used for the prediction of UTI after a stroke is about the same as previous studies (16,17,29).…”
Section: Interleukin-6 Nihss Score and Sexsupporting
confidence: 74%
“…The incidence of urinary tract infection is about 19% (10). In addition, the occurrence of infection can further aggravate the physical damage caused by stroke, and this process will form a vicious circle with stroke (11)(12)(13)(14)(15)(16). The circle will lead to a worse clinical prognosis (7,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we also measured the levels of inflammatory markers in blood; we found that patients with ALI had much higher levels of inflammatory markers than patients without ALI (Table S1 in Supplementary Material), and additional analysis showed a positive correlation between blood glutamate levels and IL-6 levels during hospitalization (Figure S3 in Supplementary Material). After brain injury, the activation of the sympathetic nervous system and the hypothalamic–pituitary–adrenal axis has been shown to be associated with the development of systemic inflammatory complications ( 36 , 37 ); however, it is noteworthy that in patients without ALI but who were diagnosed with a complicated chest infection, even though inflammatory mediator levels in these patients were similar to those in patients with ALI, the mean glutamate levels in these patients were much lower (Figure S2A in Supplementary Material). In addition, our previous animal experiments demonstrated that high concentrations of blood glutamate mediate interactions between the adenosine A 2A receptor and the metabotropic glutamate receptor 5 on neutrophils, thereby inducing the release of inflammatory mediators ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] The results of our study found that interleukin-6 might be used for the prediction of UTI after a stroke is about the same as previous studies. [ 16 , 17 , 29 ]…”
Section: Disscussionmentioning
confidence: 99%
“…[ 10 ] In addition, the occurrence of infection can further aggravate the physical damage caused by stroke, and this process will form a vicious circle with stroke. [ 11 16 ] The circle will lead to a worse clinical prognosis. [ 7 , 17 20 ]…”
Section: Introductionmentioning
confidence: 99%